PENGARUH KOMUNIKASI DAN KECERDASAN EMOSIONAL DALAM MENINGKATKAN KINERJA PEGAWAI (Studi Kasus pada Pegawai Dinas Kesehatan Kabupaten Sumenep) - Subijanto; Fatimah Riswati; Adi Mulyono (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
The Purpose of study are 1). To describe the Sumenep District Health Office. 2). To test and analyze whether communication and emotional intelligence partially have a significant effect on the performance of the employees of the Sumenep District Health Office. 3). To test and analyze whether communication and emotional intelligence simultaneously have a significant effect on the performance of the employees of the Sumenep District Health Office. 4). To test and analyze which variables between communication and emotional intelligence have a dominant influence on the performance of the employees of the Sumenep District Health Office. This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 142 employees. The results showed that 1). Partially, communication and emotional intelligence are responded very well by respondents so that they have a significant effect on the performance of the employees of the Sumenep District Health Office, proven to be true and the hypothesis is accepted. 2). Simultaneously, communication and emotional intelligence are responded very meaningfully / very well by the respondents so that they have a significant influence on the performance of the employees of the Sumenep District Health Office, it is proven and the hypothesis is accepted. 3). Communication has a dominant influence on the performance of the employees of the Sumenep District Health Office, proven to be true and the hypothesis is accepted.